Tindak Tutur Direktif Penjual Online Pakaian Muslimat di Media Sosial Facebook - Suci Fitriani; Johan Amir; Muhammad Saleh (SOCIETIES: Journal of Social Sciences and Humanities, 2023)
Abstract: Directive Speech Acts Online Sellers Clothing Muslimat on Social Media Facebook. This study aims to describe the form, function, and strategy of directive speech acts in online sellers of Muslim clothing on Facebook social media. This type of research is qualitative research. The results of the study revealed that the form of directive speech acts used by online sellers of Muslim clothing on Facebook social media were declarative, imperative, and interrogative directive speech acts. The functions of directive speech acts used by online sellers of Muslim clothing on Facebook social media are commands, invitations, requests, advice, criticism, and prohibitions. Then the speech strategies used by online Muslim clothing sellers when peddling their sales on Facebook social media are direct directive speech strategies and indirect directive speech strategies. Keywords: speech act, directive, form, function, strategy